35.9k views
5 votes
The solution to the equation log2x + log2(x – 6) = 4 is x =

User Smoreno
by
5.9k points

2 Answers

4 votes

Answer:

solution to the equation is 8

Explanation:

User Techsu
by
5.7k points
1 vote

Answer:

Value of x=8

Explanation:

Given :
log_2x+log_2(x-6)=4

To find : The solution to the equation given

Solution :

Step 1- Write the given expression


log_2x+log_2(x-6)=4

Step 2 - Using logarithmic laws


log_(b)x+log_by=log_bxy


log_2(x)(x-6)=4

Step 3 - To remove log-base 2, we need to raise the left and right hand terms to power 2.


(x)(x-6)=2^4


x^2-6x-16=0

Step 4 - Solve the quadratic equation


x^2-8x+2x-16=0


x(x-8)+2(x-8)=0


(x-8)(x+2)=0

Either x=8 or x=-2

We neglect x=-2 because negative value is not defined in log.

Value of x=8

User Wasimbhalli
by
5.2k points